MARKETPLACE SYSTEM DEVELOPMENT ON VIRTUAL MARKET SYSTEM (SUB SYSTEM: BUYING, PAYMENT, AND TRACKING) - Marcel Harjono - NIM : 13513056 , Octavianus
As the needs to easily get products and to easily distribute products increase, information technology can be an alternative solution for it. By the power of the Internet, the technology allows us to develop a universally-accessible marketplace system without any time boundary. However, only few marketplaces focus on selling products that traditional market sells. Hence, this final project will focus on developing a marketplace system that provides transaction from traditional market by the help of local government to monitor the system. The system will take Payakumbuh City as its case study's object and will focus on three parts: buying module, payment module, and tracking module. The software development's life cycle used in this project is waterfall method. Its goal is to create a system that can provide a virtual place for sellers on traditional markets to sell. By applying this system in Payakumbuh, it is expected to make buying-and-selling activities easier for buyers, sellers, delivery agents, and administrators. This system enables the local government, as the administrator, to select and filter the official sellers of the system to ensure the product's quality. By ensuring the quality, it can widely introduce the product to a national scope. That way, the sellers' income and the products' popularity will increase. System is developed using web-based application (TypeScript, AngularIO framework) so that it can be accessed using smartphone and desktop device, and the data-processing is centrally done in system database (PostgreSQL) which is managed by the system’s backend (PHP, Laravel framework). System testing is done based on functional requirement and nonfunctional requirement. Functional requirement testing is done by testing the system’s functionalities using several scenarios by user’s input and procedures, then the result from the system is compared to expected result. Nonfunctional requirement testing is done by exploration, analyses, and comparation. Marketplace system development, especially on buying module, payment module, and tracking module, is successfully developed, and based on testing result, it has fulfilled the system’s needs within system boundary.